Язык как источник сведений о национальной картине мира (Филолошке студије, 2019)
The Sapir-Whorf hypothesis is holding that the grammar and the vocabulary of a language affect the perceptions of reality and influence thought patterns and worldviews. Similar ideas have been formulated by Leo Weisgerber in Germany in the first half of the 20th century. The hypothesis of Sapir, Whorf and Weisgerber has been heavily criticised. Nevertheless, the Language Relativity hypothesis is becoming more and more popular in the modern Russian linguistics. This Renaissance constrains to find some additional arguments against the idea that the knowledge about the culture can be derived from the language and that the language can be regarded as a source for finding a specific worldview.